2023
DOI: 10.3389/fgene.2023.1104732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the structures and topologies of plasma extracted circulating nuclear and mitochondrial cell-free DNA

Abstract: Introduction: The function, origin and structural features of circulating nuclear DNA (cir-nDNA) and mitochondrial DNA (cir-mtDNA) are poorly known, even though they have been investigated in numerous clinical studies, and are involved in a number of routine clinical applications. Based on our previous report disproving the conventional plasma isolation used for cirDNA analysis, this work enables a direct topological comparison of the circulating structures associated with nuclear DNA and mitochondrial cell-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
(145 reference statements)
0
3
0
Order By: Relevance
“…That said, it should be noted that we observed in each group of COVID-19 infected patients an imbalance between the cir-nDNA and cir-mtDNA amounts. Since cir-mtDNA amount mainly corresponds to the number of circulating cell-free mitochondria, our observation 52 , 53 attests to a lower mitochondria production arising from impaired mitochondrial protein synthesis or some other mitochondrial dysfunction in COVID-19 and long COVID patients. 27 This postulate should be placed in the context of previous reports associating mitochondria dysfunction with COVID-19.…”
Section: Discussionmentioning
confidence: 65%
“…That said, it should be noted that we observed in each group of COVID-19 infected patients an imbalance between the cir-nDNA and cir-mtDNA amounts. Since cir-mtDNA amount mainly corresponds to the number of circulating cell-free mitochondria, our observation 52 , 53 attests to a lower mitochondria production arising from impaired mitochondrial protein synthesis or some other mitochondrial dysfunction in COVID-19 and long COVID patients. 27 This postulate should be placed in the context of previous reports associating mitochondria dysfunction with COVID-19.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, it is difficult to determine if cir-mtDNA is associated with NETs formation. Moreover, we have previously shown that our standard cirDNA extract is composed in healthy individuals of ∼24.3% cir-mtDNA which mostly derives from circulating cell-free mitochondria and to a much lesser extent from small extracellular vesicules, exosomes, and proteins complexed with mitochondrial DNA [ 51 ]. We are therefore inclined to think that surgery or administered therapeutics or anesthetics could induce mitochondrial injury or mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of Q-PCR amplification was made by melt-curve differentiation. Note that we quantify cirDNA from different origins, and to ease manuscript reading we use the “cir-nDNA” abbreviation for circulating cell-free nuclear DNA and the “cir-mtDNA” abbreviation for circulating mitochondrial DNA, which showed very different physical characteristics and biological stability [ 1 , 51 ].…”
Section: Methodsmentioning
confidence: 99%